Estimation of vitamin D status in infants with obesity - Tokarchuk, N. I.; Vyzhha, Yu. V. (Zaporozhye Medical Journal, 2019)
The aim of the study was to assess the status of vitamin D, bone metabolism and the role of VDR gene mononucleotide polymorphism Bsm I in infants with obesity. Materials and methods. Complex clinical and laboratory examinations of 120 children aging from 3 to 12 months were conducted. The main study group consisted of 90 infants whose physical development was above normal for age. The control group consisted of 30 infants whose physical development fell within standard deviation. The serum amounts of 25(OH)D and osteocalcin were measured for all the patients. Polymorphic variants of VDR – rs1544410 (Bsm I, A/G transition) was evaluated by PCR-RLFP. Results. The main group infants had a significant difference in the levels of vitamin D. Obese infants had the lowest serum levels of 25(OH)D. An increase in vitamin D deficiency was associated with significant decrease in serum osteocalcin. A significant negative correlation between serum 25(OH)D and body mass index has been found in infants with the highest values in children with obesity. It was also shown that the alleles and the genotype of VDR gene influence the serum amount of vitamin D. Conclusions. Obese infants have a higher risk of vitamin D deficiency compared to overweight children, those who had the risk of overweight and normal for age physical development. Among all the examined children, bone metabolism intensity according to serum osteocalcin was significantly lower in obese children as compared to children who had the risk of overweight and normal physical development. Homozygous children for mutant allele B had higher risk of vitamin D deficiency with the lowest content of serum 25(OH)D compared to heterozygous and homozygous for allele b carriers.